SAFETY OF TIROFIBAN FOR PATIENTS WITH ACUTE ISCHEMIC STROKE IN ROUTINE CLINICAL PRACTICE - Yan-Jun Zhang; Qing Liu; Qin Zhan; Qiong Li (Российский кардиологический журнал, 2014)
Aim. This work aims to study the safety of tirofiban alone and in combination with various treatments in acute ischemic stroke (AIS).Material and methods. 120 AIS patients were included in this study. There were 3 groups as below: Group A (tirofiban alone, n=68), Group B (tirofiban plus thrombolytic therapy, n=26), and Group C (tirofiban plus bridging therapy, n=26). Risk factors, stroke severity, initial imaging, treatment regimens, complications and longterm outcomes were analyzed.Results. Eight patients (6,7%) in Group A, 6 patients (23,1%) in Group B and 2 patients (7,7%) in Group C had hemorrhage during or after treatment. Sixteen patients (6 in Group A, 8 in Group B and 2 in Group C) died during hospital admission. The mortality rate was 13,3% (8,8% for Group A, 30,7% for Group B and 7,7% for Group C, respectively) in the acute phase. A favorable outcome (mRS 0–2) at the first three months after stroke was only observed in 43,3% of patients (44,1% in Group A, 46,7% in Group B and 36,4% in Group C). The average Barthel index was 72,3 in Group A, 84,4 in Group B and 56,8 in Group C (total score: 71,0).Conclusion. The stroke treatment with tirofiban is safe in AIS. A large randomized controlled trial in the future will be needed to decrease the minor bleeding complication of tirofiban therapy.